Interdependent supply relationships as institutions: The role of HR practices - Koulikoff-Souviron, Marie; Harrison, Alan (Emerald Group Publishing Limited, 2008)
This paper aims to use institutional theory to explore the role of human resource (HR) practices as carriers in the evolution of interdependent supply relationships. Design/methodology/approach – This is a qualitative study of an inter-firm supply relationship where the two partners were interdependent as a result of a “closed loop” supply relationship. The paper explores the perspectives of employees at multiple levels within both partners, and collects pluralist evidence from 36 interviewees from both sides of the dyad. It collects documentary evidence such as minutes, contractual agreements and HR documents. This paper re-analyses the evidence from earlier work using an institutional theory framework. Findings – Using Scott's “three pillars” the paper shows that HR practices can act as carriers of regulative, normative and cultural-cognitive elements in interdependent supply relationships through both formal and informal mechanisms. Regulative elements were less evident, but could be fundamental in shaping the other two. A tension was found between institutional pressures at the inter- and intra-firm levels, an emergence of innovative practices and new routines at inter-organizational level, and an evolution over time that could involve a de-institutionalisation of the relationship as a result of internal priorities competing with the resource requirements of the supply relationship. Originality/value – The paper addresses the interface between OM and organisational theory. Areas are proposed where institutionalisation of a supply relationship can be strengthened or weakened. The findings further challenge the view of supply relationships as a “spectrum” in which progress is unidire
Keywords: Buyer-seller relationships; Human resource strategies; Operations management; Organizational theory